Evaluating the Impact of Generative Artificial Intelligence on Learning Processes in Higher Education: A Quantitative Comparative Study - Araujo, Rene L.; Mamani, Godofredo Quispe; Jiménez-Pitre, Iris (Journal of Posthumanism, 2025)
This study analyzes the impact of generative artificial intelligence (AGI) on learning processes in higher education institutions through a comparative quantitative approach. We worked with two groups of university students: one with access and training in the use of IAG tools, and the other without exposure to these technologies. Standardized tests and perception questionnaires were applied to measure academic performance, autonomy in learning, and conceptual clarity. The results show significant improvements in the experimental group, showing that the IAG can have positive effects if it is used for pedagogical purposes. The study also points to associated risks, such as technological dependence and the uncritical use of AI-generated content.